Isolated progression of metastatic lung cancer: Clinical outcomes associated with definitive radiotherapy. Issue 20 (30th July 2020) - Friedes, Cole; Mai, Nicholas; Fu, Wei; Hu, Chen; Hazell, Sarah Z.; Han, Peijin; McNutt, Todd R.; Forde, Patrick M.; Redmond, Kristin J.; Voong, K. Ranh; Hales, Russell K.
Abstract : Background: Progressive, metastatic non–small cell lung cancer (NSCLC) often requires the initiation of new systemic therapy. However, in patients with NSCLC that is oligoprogressive (≤3 lesions), local radiotherapy (RT) may allow for the eradication of resistant microclones and, therefore, the continuation of otherwise effective systemic therapy. Methods: Patients treated from 2008 to 2019 with definitive doses of RT to all sites of intracranial or extracranial oligoprogression without a change in systemic therapy were identified. Radiographic progression‐free survival (rPFS) and time to new therapy (TNT) were measured. Associations between baseline clinical and treatment‐related variables were correlated with progression‐free survival via Cox proportional hazards modeling. Results: Among 198 unique patients, 253 oligoprogressive events were identified. Intracranial progression occurred in 51% of the patients, and extracranial progression occurred in 49%. In the entire cohort, the median rPFS was 7.9 months (95% CI, 6.5‐10.0 months), and the median TNT was 8.8 months (95% CI, 7.2‐10.9 months). On adjusted modeling, patients with the following disease characteristics were associated with better rPFS: better performance status ( P  = .003), fewer metastases ( P  = .03), longer time to oligoprogression ( P  = .009), and fewer previous systemic therapies ( P  = .02). Having multiple sites of oligoprogression was associated with worse rPFS ( P  < .001). Conclusions: In select patients with oligoprogression, definitive RT is a feasible treatment option to delay the initiation of next‐line systemic therapies, which have more limited response rates and efficacy. Further randomized prospective data may help to validate these findings and identify which patients are most likely to benefit. Abstract : Treating metastatic, oligoprogressive lung cancer with ablative radiotherapy delays the time to next therapy by 8.8 months. Patients with favorable indolent disease characteristics are most likely to benefit from this therapy.